Cutaneous lymphomas: An update - Ashok Singh; Sudheer Arava; M K Singh (Wolters Kluwer Medknow Publications, 2014)
Cutaneous lymphomas are heterogeneous and distinct entities which have been in controversy since the time of conception. WHO EORTC defined them as distinct pathological entity compared to the nodal counterpart. They are defined as lymphomas having primary cutaneous presentation without any systemic involvement. As such the diagnosis of cutaneous lymphomas is a diagnosis of exclusion. These lymphomas are distinct from the nodal lymphomas in their presentation, behaviour and prognosis. These lymphomas have been divided into B cell and T cell type based on the presence of predominance of atypical lymphocytes of B or T lineage. The most common cutaneous lymphomas are T cell immunophenotype, and Mycosis fungoides constitutes the majority of cutaneous lymphomas. Cutaneous lymphomas needs to be differentiated from pseudolymphomas which are benign proliferation of lymphoid cells mimicking lymphomas and mostly have a benign course